Design and Analysis of a Typical Vertical Pressure Vessel Using ASME Code and FEA Technique - Kristaq Hazizi; Mohammad Ghaleeh (Designs, 2023)
This study aims to address the hazards associated with the design and manufacture of pressure vessels used for storing dangerous liquids, specifically focusing on the increased demand for liquefied petroleum gas (LPG) worldwide. The construction of more LPG facilities necessitates the implementation of safer pressure vessels to mitigate risks such as explosions and leakage. The primary objective of this project is to design a vertical pressure vessel, in accordance with the American Society of Mechanical Engineers (ASME) code, capable of safely storing 10 m3 of pressurised LPG. To ensure the safety of the pressure vessel, the researchers employed Autodesk Inventor Professional 2023 for geometric modelling and utilised Inventor Nastran for finite element analysis (FEA) to investigate displacements, deflections, and von Mises stresses. The vessel is cylindrical in shape and features two elliptical heads, two nozzles, a manway, and four leg supports. The FEA analysis conducted using Autodesk Inventor Nastran enabled the researchers to identify areas where structural modifications were necessary to reduce stress within the vessel. The results revealed an inverse relationship between the displacement and the tank section shell thickness. Additionally, the factor of safety exhibited a linear increase as the shell thickness increased. The researchers carefully considered permissible pressures and determined the required wall thickness to maintain acceptable maximum stresses. The findings indicate that the design of the pressure vessel is safe from failure. Among the components, the manway experiences the highest stresses, followed by the shell, while the heads, nozzles, and leg supports experience lower stresses. The researchers also conducted theoretical calculations for the entire model and ensured that the results fell within acceptable limits, further validating their design approach. The research emphasised the importance of designing pressure vessels in compliance with ASME codes to ensure safety and prevent hazards associated with improper design and manufacturing. The combination of Autodesk Inventor Professional and Inventor Nastran proved to be an effective approach for simulating and evaluating the performance of the pressure vessel. Through the analysis, the researchers found that changes to the pressure vessel structure were necessary to reduce stress. They observed an inverse relationship between displacement and tank section shell thickness, while the factor of safety increased linearly with shell thickness. Stress distribution analysis revealed that the manway and shell experienced the highest stresses, while the heads, nozzles, and leg support exhibited lower stresses. Employing the finite element method, potential stress points within the pressure vessel were identified, enabling necessary modifications to enhance its safety.